Internalization of Socio-Cultural Values Through History Learning in Class X of SMA Semesta Semarang - Nindhika, Claudea Cici; Bain, Bain; Sodiq, Ibnu (Universitas Negeri Semarang, 2021)
This research aimed to find out and analyze the learning process of history in SMA Semesta Semarang, find out and explore the implementation of socio-cultural values through history learning, and find out and examine the internalization of socio-cultural values in history learning in SMA Semesta Semarang. This method of this research is a descriptive qualitative. The subject of this research was the history teachers of grade X in SMA Semesta Semarang. The data collection was done using observation techniques, interviews, and documentation. In determining the validity of the data, this study used source triangulation. The data analysis technique was an interactive model for data reduction, presentation, and conclusion. The results showed that history learning in SMA Semesta Semarang had been running well. Before starting the learning activities, teachers first prepare a lesson plan. The lesson plan referred to Curriculum 2013. The teachers used the CTL (Contextual Learning) model and the lecturing method in the learning process. The implementation of socio-cultural values through historical learning was done by teachers spontaneously in the learning activities, and it was not written in the lesson plan. Internalization of the values of character education in the learning process was done through the learning activities in or outside the school. The process of internalizing socio-cultural values through the learning activities in the classroom was divided into three stages: Transformation, Transaction, and Trans-internalization. The internalization of socio-cultural values outside of the classroom learning activities was done through various school activities and habituations such as the presence of honest canteens, religious activities, and visiting historical places—keywords: internalization; values; social-culture.